COVID-19 and Mental Health of Individuals with Different Personalities - Eugenio Proto; Anwen Zhang (Institute of Labor Economics (IZA), 2021)
Several studies have been devoted to establishing the effects of the Covid-19 pandemic on mental health across gender, age and ethnicity. However, much less attention has been paid to the differential effect of lockdown according to different personalities. We do this using the UKHLS longitudinal dataset, representative of the UK population. The UKHLS dataset allows us to assess the mental health of the same respondent during the Covid-19 period and the year before based on their personality "Big Five" traits and cognitive skills. We find that during the Covid-19 period individuals who have more Extrovert and Open personality report a higher mental health deterioration, while the ones scoring higher in Agreeableness are less affected. The effect of Openness is particularly strong: one more standard deviation predict one more symptom on the GHQ12 test for about 1 respondent over 4. In female respondents, Cognitive Skills and Openness are particularly strong predictors of deterioration. Neuroticism seems to predict more mental health deterioration, as it is normal to expect, but this effect is not significant in the main specifications of the estimated model. The study's results are robust to the inclusion of potential confounding variables such as changes in: physical health, household income and job status (like unemployed or furloughed).
Keywords: I3; 330; COVID-19; mental health; Big 5; cognitive skills